THE MEANING OF STORYTELLING PRACTICES IN STRENGTHENING RELIGIOUS CHARACTER IN ELEMENTARY SCHOOL STUDENTS: A PHENOMENOLOGICAL STUDY - Akhmad Mohammad Afifudin; Wakhudin Wakhudin; Subuh Anggoro; Ine Kusuma Aryani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to uncover the meaning of storytelling practices in strengthening the religious character of elementary school students, with a novelty in the meaning of storytelling as a lived pedagogical experience that shapes the process of internalizing religious values ​​at each stage. The qualitative research method used a phenomenological design at SDN 2 Plorengan and SDIT Al Ihsan, Banjarnegara. Participants consisted of 3 teachers, 6 students, and 2 principals. Data were collected through observation, interviews, and documentation. Data were analyzed using an interactive model of condensation, presentation, and verification. Data were validated through triangulation of techniques, sources, and member checking. The results show that storytelling practices can connect spiritual, moral, and social dimensions in strengthening the religious character of elementary school students. Through interrelated stages from preparation to closing, students not only understand religious values ​​in their relationships with God, themselves, and others, but also reflect on and apply them in their daily lives. Thus, storytelling is interpreted as a pedagogical experience that shapes the understanding and practice of religious values. Therefore, teachers need to develop storytelling practices as learning experiences to strengthen character